2011
DOI: 10.1007/s10898-011-9713-2
|View full text |Cite
|
Sign up to set email alerts
|

An exact solution method for unconstrained quadratic 0–1 programming: a geometric approach

Abstract: We explore in this paper certain rich geometric properties hidden behind quadratic 0-1 programming. Especially, we derive new lower bounding methods and variable fixation techniques for quadratic 0-1 optimization problems by investigating geometric features of the ellipse contour of a (perturbed) convex quadratic function. These findings further lead to some new optimality conditions for quadratic 0-1 programming. Integrating these novel solution schemes into a proposed solution algorithm of a branch-and-bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…Ahlatçıoglu et al [1] proposed to combine QCR and the convex hull relaxation to solve problem (BQP). The geometric investigation in Li et al [36] for binary quadratic programs provides some theoretical support for QCR from another angle. Billionnet et al [9] extended the QCR approach to general mixed-integer programs by using binary decomposition.…”
Section: Combination Of Lift-and-convexification and Qcrmentioning
confidence: 98%
See 1 more Smart Citation
“…Ahlatçıoglu et al [1] proposed to combine QCR and the convex hull relaxation to solve problem (BQP). The geometric investigation in Li et al [36] for binary quadratic programs provides some theoretical support for QCR from another angle. Billionnet et al [9] extended the QCR approach to general mixed-integer programs by using binary decomposition.…”
Section: Combination Of Lift-and-convexification and Qcrmentioning
confidence: 98%
“…If the objective function of (P(u, v, w, t)) is convex, by the strong duality of convex quadratic programming (see, e.g., Proposition 6.5.6 in [5]), the optimal values of (P(u, v, w, t)) and (36) are equal. Thus, we have shown that problem (MAXuvwt) is equivalent to an SDP problem in the form of (SDP a ).…”
Section: Theoremmentioning
confidence: 99%
“…对于一般的 0-1 二次优化问题, 学者们提 出了求解精确解的多种方法, 包括基于代数的方法、线性化方法、割平面算法和分支定界算法等. 文 献 [370,378] [362,379,380]). [327] 使用上述半定规划 松弛给出最大割问题 0.8756 的近似界.…”
Section: 非线性整数优化unclassified
“…To solve a QUBO problem, a number of exact methods have been developed [5,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. However, due to the computational complexity of the problems, these approaches have only been able to solve smallsized instances.…”
Section: The Problem and Previous Workmentioning
confidence: 99%